PERANAN PERSATUAN BATAK TOBA DALAM MEWARISKAN ADAT PERKAWINAN MASYARAKAT BATAK TOBA DI SEBANGA DURI - Siregar, Rinaldi Afriadi; ', Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The development of the times affects the occurrence of change and causes various problems arise in the marriage customs of the Batak Toba community. Such amendment adds or reduces the obligations in marriage customs. The implementation of the marriage customs of the Batak Toba community was carried out in a long time and process, now shortened by the customary term ulaon realize (a feast that was completed for a day). In addition, the indigenous Batak Toba people in Sebanga were rarely / not intermarried but the Toba Batak community in Sebanga allowed their children to marry other tribes because the average Batak Toba community in Sebanga wandered and married with local women, and supported by women Toba Batak used to be rare in Sebanga, Duri. By having feelings and love for Toba Batak culture, Batak Toba society in Sebanga Duri founded a community named Perbato (Batak Toba Association). The purpose of this study is to determine the factors behind the formation of Perbato in Sebanga Duri, knowing how the role of Perbato in inheriting the marriage customs of the Batak Toba community in Sebanga Duri, knowing how the Toba Batak people in Sebanga Duri look at the existence of Perbato, knowing how the role of Perbato as a mediator for Completion of Toba Batak marriage customary problem in Sebanga Duri. The method used is Qualitative Approach. The research location was Sebanga, Duri. The time of study from the start of the proposal seminar to the thesis examination. The results of this study indicate that the role of Perbato in inheriting the marriage customs of Batak Toba community is something that can not be separated during the marriage ceremony which is legitimate according to the tradition of Batak Toba community in Sebanga Duri.Keywords: Role, Perbato, Inherit, Marriage, Toba Batak.